Ferramentas moleculares aplicadas ao estudo de parasitas emergentes em Leishmaniose visceral - Takamiya, Nayore Tamie (2023)
Leishmaniases are neglected tropical diseases considered important to public health. Visceral Leishmaniasis (VL) is the most severe form of the disease, which affects organs such as spleen, bone marrow, liver and lymph nodes. It is caused by Leishmania infantum in Brazil. Advances in Molecular Biology tools have provided alternatives for diagnostics at research reference centers. Studies have demonstrated the presence of monoxenous trypanosomatids (Leptomas spp. and Crithidia spp.) in the clinical spectrum of Leishmaniasis. The clinical implications of these trypanosomatid species in Leishmaniasis are unknown, and the impact of these infections has rarely been studied. Further research is necessary to identify and investigate these species. Therefore, this work presented two goals to advance knowledge about this emerging VL parasites. The first one was to identify new species-specific genes able of discriminating between L. infantum and Crithidia sp. in clinical and experimental samples. The secod one was to obtain genetically modified strains of parasites expressing fluorescent reporter genes through genetic engineering and cell transfection techniques, such as the green fluorescent protein (GFP) gene in Crithidia sp. LVH60A (strain LVH60a_C1) and mCherry in the HUUFS14 strain of L. infantum. Primers designed to identify L. infantum (LinJ31seq and LinJ31_2420) and Crithidia sp. (Crid2.1seq, LVH60_Tig001, and Catalase-LVH60_12060_1F) showed a good performance of detection. These primers have been extensively validated, both for species identification (qualitatively) and for estimation of parasite load (quantitatively) in experimental and clinical VL samples, covering a variety of vertebrate hosts. Through molecular screening and analysis of 62 clinical isolates from VL patients using these species-specific genes, it was possible to identify 51 parasite cultures with positive PCR results for Crithidia sp. Interestingly, qPCR assays indicated co-infection of L. infantum with Crithidia sp. LVH60A in two new cases of VL in Sergipe. Furthermore, by re-evaluating clinical samples from a case of VL from Sergipe published in 2019, it was found that the patient was co-infected with these two species of trypanosomatids. With the cell transfection experiments, it was possible to transform the HUUFS14 strain (L. infantum) expressing the fluorescent gene mCherry, presenting phenotypic characteristics similar to those of the wild-type strain and keeping infective capacity in in vitro infection assays. The transfection protocols tested in this study were inefficient for the transformation of Crithidia sp. LVH60A, highlighting the peculiarities of the parasite. Overall, this study was important in establishing new molecular targets that can be used to improve the diagnosis of VL. Furthermore, such targets show promise for future investigations, aiming to deepen our understanding of the role of monoxenic trypanosomatids in VL pathology and/or as potential emerging parasites.